2012
DOI: 10.1177/875687051203100204
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Effectiveness of Web Conferencing Software in the Digital Environment to Deliver a Graduate Course in Applied Behavior Analysis

Abstract: This article provides an overview of the planning and instructional delivery of a course in Applied Behavior Analysis using Adobe Connect Pro™. A description of software features used by course instructors is provided along with how each feature compares to resources found to deliver instruction in a traditional classroom setting. In addition, the article describes the results and implications from instructional delivery designed to increase student participation, correct responding, and levels of satisfaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 42 publications
1
26
0
Order By: Relevance
“…Such null findings between live and webcast information are consistent with longstanding findings on the use of distance vs. in-person education on academic performance (Shachar & Neumann, 2010). More recently, distance-education has extended to special education, with examples including the delivery via distance technology of a graduate course in applied behavior analysis (Hudson, Knight, & Collins, 2012) and of professional development trainings to rural special educators (Erickson, Noonan, & McCall, 2012). In each case, distance attendees learned similar amounts of information as did attendees attending in person.…”
Section: Discussionmentioning
confidence: 99%
“…Such null findings between live and webcast information are consistent with longstanding findings on the use of distance vs. in-person education on academic performance (Shachar & Neumann, 2010). More recently, distance-education has extended to special education, with examples including the delivery via distance technology of a graduate course in applied behavior analysis (Hudson, Knight, & Collins, 2012) and of professional development trainings to rural special educators (Erickson, Noonan, & McCall, 2012). In each case, distance attendees learned similar amounts of information as did attendees attending in person.…”
Section: Discussionmentioning
confidence: 99%
“…In 70% of the 125 studies included in the meta‐analysis, students taking courses by distance education (vs. by live instruction) made greater educational gains. Although Shachar and Neumann () only examined distance technology with respect to student performance, distance technology has also been used in special education specifically in courses that target teacher professional development (Erickson, Noonan, & McCall, ) and behavior analysis (Hudson, Knight, & Collins, ). It may be that distance education (vs. traditional) courses appeal to a greater number of learning style preferences (i.e., visual, auditory, and kinesthetic) thereby making distance education more likely to improve learning retention (Bull & Kay, ; Rogers, ).…”
Section: Introductionmentioning
confidence: 99%
“…Within teacher education, online learning offers significant potential for accessible, convenient and cost-effective professional development (Fernández, 2007). This may be particularly germane to teacher professional development for inclusive and special education where there may be a shortage of qualified personnel and where access to specialized accredited postgraduate programmes may be problematic, particularly for teachers living in remote rural areas ( [2]). In the higher education institution in which the authors work, this need to widen access for teachers living in remote areas in the Republic of Ireland was a significant factor driving the development of blended and online programmes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Technological advances over the past decade have provided higher education institutions offering distance education programmes with a much greater range of options with which to communicate and interact with students ( [1], Hudson, Knight & Collins, 2012;McBrien, Jones & Cheng, 2009). In particular, it has been suggested that Web2 technologies offer the potential to facilitate synchronous interaction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation